Comparison of Inferior Vena Cava Distensibility Index and Pulse Pressure Variation as Predictors of Fluid Responsiveness in Sepsis Patients at the ICU - Evandrian, Difa Aulia; Soesilowati, Danu; Rakhmajati, Pradana Bayu (Perhimpunan Dokter Spesialis Anestesiologi dan Terapi Intensif, 2026)
Background: Sepsis is a major global health challenge with an estimated 49 million incident cases and 11 million deaths each year, which requires appropriate fluid management to improve patient prognosis.Objective: This study aims to compare the effectiveness of the inferior vena cava distensibility index (IVC-DI) and pulse pressure variation (PPV) as predictors of fluid responsiveness in sepsis patients in the intensive care unit (ICU).Methods: This study used an experimental design with a sample of 36 sepsis patients selected through consecutive sampling. Fluid administration of 500 ml RL was carried out for 15 minutes, followed by measurement of IVC-DI and PPV, and evaluation of an increase in stroke volume (SV) > 15% as an indicator of fluid responsiveness.Results: The study showed that PPV had a sensitivity of 93% and specificity of 90%, with a positive predictive value of 87.5% and a negative predictive value (NPV) of 95%. The overall accuracy of PPV was 91.6%. PPV showed a very strong correlation with SV increase > 15% (r = 0.832, p < 0.001). On the other hand, IVC-DI had a sensitivity of 80% and specificity of 71%, with a positive predictive value of 66% and a NPV of 83%. The overall accuracy of the IVC-DI was 75%. The IVC-DI showed moderate correlation with SV increase > 15% (r = 0.507, p = 0.002). Inter-observer agreement in IVC-DI measurements also showed excellent results with a Kappa value of 1.00, indicating perfect agreement. From the results of this study, PPV proved to be more accurate in predicting fluid responsiveness compared to IVC-DI in sepsis patients in the ICU. These two methods, although equally useful, showed different levels of effectiveness in this clinical context.Conclusion: PPV showed better performance than IVC-DI in predicting fluid responsiveness in mechanically ventilated sepsis patients in the ICU. PPV demonstrated higher accuracy, sensitivity, specificity, and a stronger correlation with SV improvement, indicating that PPV may serve as a more reliable predictor in this clinical setting.